Precariousness in employment mediated by digital platforms. Evidence from Europe - María Isabel de Andres; Emilio Congregado; María Concepción Román (Revista de Economía Mundial, 2024)
Is precarity inherent to employment when it is mediated by a digital platform, or does employment precarity have other causes? Using the first wave of the European survey on collaborative economy and employment (COLLEEM, hereinafter), we identify different types of precarity among platform workers by using different operationalizations of this phenomenon. Our results indicate that i) the probability of precarity in on-demand platform work varies according to the type of employment and to certain sociodemographic characteristics; ii) findings are sensitive to the dimension of precarity that we address; and iii) self-employed individuals and those workers who access digital platform jobs as last resort have a more positive perception of working conditions in the sector than salaried employees and those whose reason for entry was not the lack of alternative employment. The study provides guidelines for the effective design of mitigation policies to protect workers in the digitalized EU labour market.